Arabidopsis Class II Formins AtFH13 and AtFH14 Can Form Heterodimers but Exhibit Distinct Patterns of Cellular Localization - Kollárová, Eva; Baquero Forero, Anežka; Stillerová, Lenka; Přerostová, Sylva; Cvrčková, Fatima (International journal of molecular sciences, 2020)
Formins are evolutionarily conserved multi-domain proteins participating in the control of both actin and microtubule dynamics. Angiosperm formins form two evolutionarily distinct families, Class I and Class II, with class-specific domain layouts. The model plant Arabidopsis thaliana has 21 formin-encoding loci, including 10 Class II members. In this study, we analyze the subcellular localization of two A. thaliana Class II formins exhibiting typical domain organization, the so far uncharacterized formin AtFH13 (At5g58160) and its distant homolog AtFH14 (At1g31810), previously reported to bind microtubules. Fluorescent protein-tagged full length formins and their individual domains were transiently expressed in Nicotiana benthamiana leaves under the control of a constitutive promoter and their subcellular localization (including co-localization with cytoskeletal structures and the endoplasmic reticulum) was examined using confocal microscopy. While the two formins exhibit distinct and only partially overlapping localization patterns, they both associate with microtubules via the conserved formin homology 2 (FH2) domain and with the periphery of the endoplasmic reticulum, at least in part via the N-terminal PTEN (Phosphatase and Tensin)-like domain. Surprisingly, FH2 domains of AtFH13 and AtFH14 can form heterodimers in the yeast two-hybrid assay-a first case of potentially biologically relevant formin heterodimerization mediated solely by the FH2 domain.
Keywords: proteiny huseníčku; Protein Binding; exprese genu; Gene Expression; Endoplasmic Reticulum; Recombinant Proteins; class II formin; Arabidopsis; Arabidopsis Proteins; endoplazmatické retikulum; confocal laser scanning microscopy; Microtubules; AtFH13; proteinové domény; rekombinantní proteiny; vazba proteinů; forminy; At1g31810; Nicotiana; Formins; dimerizace; mikrotubuly; Dimerization; FH2 domain; AtFH14; At5g58160; PTEN-like domain; Protein Domains; tabák